Human resource requirements for Peninsular Malaysia by newspaper content analysis - C. Valida, Abelardo; Regupathi, Angappan; Zalazilah, Mohd Hanizan; Jaganathan, Surinarayanan (Universiti Utara Malaysia, 1995)
Prior research in the area of human resource requirements and manpower forecasting point out that the problem lies not in the absence of sophisticated models but rather, the absence of reliable and detailed time series data (Harvey & Murphy, 1988). It appears that a rigorous monitoring and a reliable mechanism for tracking down such information is vital to provide feedback for purposes of human resource development planning (Othman Yeop, 1990). This descriptive study, therefore, sought to establish the viability of content analyzing job advertisements in leading newspapers over a ten month period in order to identify the essential attribute of the job demand, establish time-series data for such demand, and determine the trends based on the major variables, as suggested by manpower planning agencies. The results obtained using the content analysis methodology yielded similar qualitative information as those publicized by government manpower agencies.